Home of RF and Wireless Vendors and Resources

One Stop For Your RF and Wireless Need

Flipflop conversion equations-JK,SR,D,T FF conversion

This page covers flipflop(FF) conversion equations for JK FF to SR FF, SR FF to JK FF, D FF to JK FF, D FF to SR FF, D FF to T FF, SR FF to D FF, JK FF to D FF, T FF to D FF, T Flipflop to JK flipflop and JK flipflip to T flipflop conversion.

SR FF to JK FF(Flipflop) conversion equation

S = J*Qn'

R = K*Qn

SR FF to D FF(Flipflop) conversion equation

S = D

R =D'

SR FF to T FF(Flipflop) conversion equation

S = T*Q'

R = T*Q

JK FF to SR FF(Flipflop) conversion equation

J = S

K = R

JK FF to D FF(Flipflop) conversion equation

J = D

K = D'

JK FF to T FF(Flipflop) conversion equation

J = K = T

D FF to SR FF(Flipflop) conversion equation

D = S + R'*Qn

D FF to JK FF(Flipflop) conversion equation

D = J*Q' + K'*Q

D FF to T FF(Flipflop) conversion equation

D = T (ex-or) Q

T FF to JK FF(Flipflop) conversion equation

T = J*Q' + K*Q

T FF to SR FF(Flipflop) conversion equation

T = S*Q' + R*Q

T FF to D FF(Flipflop) conversion equation

T = D (ex-or) Q

Above mentioned flipflop conversion equations are very useful for converting one flipflop type to the other flipflop type.

Flipflop VHDL codes

D Flipflop
T Flipflop
JK Flipflop

RF and Wireless Terminologies


Share this page

Translate this page